AB0511 Discontinuation of Methotrexate Treatment in Patients with Rheumatoid Arthritis and Relatiomships with Candidate Single Nucleotide Polymorphisms. (9th June 2015) - Soukup, T.; Dosedel, M.; Pavek, P.; Nekvindova, J.; Kubena, A.A.; Barvik, I.; Vlcek, J.; Bradna, P.
Abstract : Background: Some single nucleotide polymorphisms (SNPs) might be predictive of methotrexate (MTX) therapeutic outcome in rheumatoid arthritis (RA). Objectives: The aim of this study was to determine whether SNPs in key MTX pathway genes might be predictive of an adverse drug reactions (ADR) and MTX discontinuation in RA patients treated with peroral MTX. Methods: There were 185 patients enrolled in the retrospective study, all of whom fulfilled the 1987 RA criteria of the American College of Rheumatology. The patients were currently or previously treated with peroral MTX. Genotyping was performed by quantitative PCR with allelic discrimination using commercial TaqMan (allele-specific) assays (Life Technologies, USA): ( ADORA2A, rs2298383), ( ADORA2A, rs3761422), ( ADORA2A, rs2267076), ( ADORA2A, rs2236624), ( AMPD1, rs17602729), ( ATIC, rs2372536), ( ITPA, rs1127354), ( MTHFD1, rs2236225), ( MTHFR, rs1801131), ( MTHFR, rs1801133), ( SLC01B1, rs4149056). Results: Clinical data were available in 185 patients: mean age 58.7 years, SD ±12.17, age of 29-85 years. 30.3% of patients were male. MTX treatment was discontinued in 33 (17.8%) patients owing to ADR (hepatopathy, n=12; infection, n=10; dyspepsia, n=9; leucopenia, n=1; alopecia, n=1). 83 patients were treated by MTX monotherapy or MTX together with glucocorticoids. Other patients were treated by MTX in a combination with conventional synthetic or biologic DMARDs. Presence and absence of ADR were evaluated in relation to the identified genotypes. We revealed no evidence to support association of the presence of ADR and the following SNPs: ATIC rs2372536, AMPD1 rs17602729, ITPA rs1127354, SNPs of ADORA2A (rs2298383, rs3761422, rs2267076, and rs2236624), MTHFD1 rs2236225, MTHFR rs1801131, MTHFR rs1801133 and SLC01B1 rs4149056. Stratification of different ADRs in ITPA 94CC and ITPA 94CA genotypes showed association with dyspepsia P=0.01 using Kendall's test, in case of MTX DMARDs monotherapy P=0.046 respectively. ITPA 94AA genotype have not been found. Conclusions: In conclusion, we found for the first time that ITPA 94CC genotype is associated with a higher risk of dyspepsia in Caucasian RA patients treated with peroral MTX. Acknowledgements: This work was supported by a research project MH CZ - DRO (UHHK, 00179906) to T.S. and supported by research project PRVOUK P37-08 (from Charles University). Disclosure of Interest: None declared